Understanding the Potential of Implementing UI GreenMetric Standards in the Universitas Bandar Lampung Campus Area - Fritz Akhmad Nuzir; Rizky Khalid; Anggi Nur Aini; Isti Mutmainah (Jurnal Arsitektur, 2023)
Campus is an area that has the potential to cause significant environmental impacts from its water use, energy consumption, waste production, use of motorized vehicles, and excessive development of facilities. Therefore, a standard or assessment guide is needed to evaluate whether the development of the campus area is in accordance with the principles of sustainable development so that the resulting environmental impact can be reduced. The UI GreenMetric Standard was developed by the University of Indonesia in 2009 with the aim of assessing higher education institutions for greening and environmental sustainability efforts in their respective campuses. There are six categories in the UI GreenMetric standard, namely: Setting and Infrastructure (SI), Energy and Climate Change (EC), Waste (WS), Water (WR), Transportation (TR), and Education and Research (ED). In this study, Campus A and Campus B areas at the Universitas Bandar Lampung (UBL) were selected as the case study to understand in general the potential for implementing assessment categories in UI GreenMetric. It is known from the UI GreenMetric assessment experiment in the UBL campus area that the total score obtained was 3,035 points. The highest score of 690 points was obtained from the ED indicator, while the lowest score with 310 points was obtained from the WR indicator. The results of this study can be used as a reference for the implementation of the principles of sustainable development at UBL as a preparation for implementing the UI GreenMetric standard.